Analysis of Well Water Quality based on Physics, Chemical, and Microbiology Parameters in IAIN Tulungagung Area - Tutik S. Wahyuni; Desi Kartikasari (Universitas Tadulako, 2020)
Water as a natural resource is needed in life. Nowadays, the need for freshwater is increasing. Meanwhile, most people fulfill their daily water needs from well water. This study aims to determine the quality of well water in the IAIN Tulungagung campus area based on physical, chemical, and biological parameters. This type of research is a quantitative descriptive. A total of 12 points from 4 stations were chosen by random sampling. Laboratory test results were compared with PerMenKes RI No. 492/MENKES/PER/IV/2010 and PerMenKes RI No. 32 Tahun 2017. The results of the study show that (1) two sources of water do not qualify as clean water based on physical parameters because the turbidity value and total dissolved solids (TDS) exceeds the quality standard, (2) five sources of water do not qualify as water clean based on chemical parameters because the Fe content exceeds the quality standard and/or low dissolved oxygen (DO) concentration, and (3) four wells do not meet bacteriological tests for the amount of coli fecal bacteria and total coliform. Well water in the IAIN campus area has decreased water quality caused by domestic waste.